Propose of project for the professional internship in the integration of an artificial intelligence model in the quality assessment of the welding spots in the car body of the cars produced by audi ag, neckarsulm, Germany - Baquero Saenz, Angelica Dahyana (Escuela Colombian de Ingeniería, 2023)
En la actualidad, el proceso de evaluación lo lleva a cabo un equipo de especialistas mediante ultrasonido para el control manual de la calidad de la soldadura en cada punto de resistencia. Como uno de los pilares de AUDI, se requiere generar una mejora de este proceso de evaluación de la calidad, procurando no sólo reducir su tiempo de aplicación, pero también el número de mano de obra necesaria. En términos generales, se requiere generar una mayor digitalización en la evaluación de la calidad a través del uso de modelos con inteligencia artificial, que le permita ser optimizado en tiempo, calidad y costo.

At present, the evaluation process is carried out by a team of specialists using ultrasound for the manual control of the welding quality at each resistance point. As one of the cornerstones of AUDI, this quality assessment process needs to be improved, aiming not only to reduce its implementation time, but also to reduce the number of manpower required. Generally speaking, it is necessary to generate greater digitalization in quality assessment through the use of artificial intelligence models, allowing it to be optimized in terms of time, quality and cost.
Keywords: Inteligencia artificial; Modelos de aprendizaje; Automatización; Inteligencia artificial; Modelos de aprendizaje; Automatización; Artificial intelligence; learning models; Automation